Isolation and characterization of novel phages targeting Xanthomonas oryzae: culprit of bacterial leaf blight disease in rice - Liu, Jian; Chia, Suet Lin; Tan, Geok Hun (Mary Ann Liebert, 2021)
Background: Bacterial leaf blight (BLB) disease caused 80% of disease incidence in paddy in Kedah and Selangor states of Malaysia. The pathogenic bacterium, Xanthomonas oryzae pv. oryzae (Xoo), is one of the destructive pathogens infecting lowland irrigated and rainfed paddy in Asia’s tropical and temperate environments. Bacteriophages (or phages) have been proposed to control the pathogen due to their efficacy and safety aspects. Material and Methods: In this study, a total of 70 Xoo-phages were isolated from termite which living in rice-growing area. Results: 2 lytic phages NF-1 and NF-3 were selected due to the high titer of the virus. Electron microscopic analysis showed that those phages belonged to the family Podoviridae, order Caudovirales with short noncontracted tails. Moreover, these phages have a narrow host range specifically target Xoo with a higher burst size. Whole-genome sequencing showed that the Xoo-phage NF-1 and NF-3 consists of a linear double-stranded DNA molecule of length 41,151 and 38,454 bp, respectively. Conclusion: This study successfully characterized two novel Xanthomonas phages and their potential as antimicrobial agents against BLB disease in rice.